Teachers Style of Optimism Public Senior High School Rimba Melintang, Rokan Hilir, Riau - Natuna, Daeng Ayub; Wilson, Wilson (Proceedings of the UR International Conference on Educational Sciences, 2018)
The style of optimism in a teacher is a positive way of thinking as a formula, paradigm, frame of mind, and system of thinking. The purpose of this study was to find and analyze the level of teacher optimism Public senior high school, Rimba Melintang, Rokan Hilir, Riau. This research is quantitative descriptive which is carried out by survey. The population is 75 and the sample of this study is 62 teachers. Data were collected by questionnaire and analyzed using descriptive statistics and inferential statistics. The results of this study found that the level of optimism of teachers was in the very high category (Mean, 4.14), and the contribution of each indicator as a factor was classified as high (60.04 percent). This finding means that the better the teachers optimism style, the positive thinking skills, being grateful and always happy with their assignments, accepting all the tasks given happily, sure there are opportunities in front of them, and always motivating others such as teachers, students, and parents students are getting better, because it is very important in realizing teachers who are profesesional in educating and teaching. It is expected that all teachers have a high and good optimism style in carrying out their professional duties as teachers to realize an effective school. It is expected that all teachers have a high and good optimism style in carrying out their professional duties as teachers to realize an effective school.